MaxEnt-based habitat suitability of the Rinjani scops-owl on Lombok, West Nusa Tenggara, Indonesia - GITO HADIPRAYITNO; GDE CAHYADI WIRAJAGAT; I WAYAN SUANA; SRI APRILILIA NUR LARASATI; BAHTIAR ARDDUN ASYAFIQ; TRI SETIA KURNIA NURI; MOHAMMAD LIWA ILHAMDI; RIZKY REGINA KAWIRIAN; PUGUH KARYANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Hadiprayitno G, Wirajagat GC, Suana IW, Larasati SAN, Asyafiq BA, Nuri TSK, Ilhamdi ML, Kawirian RR, Karyanto P. 2026. MaxEnt-based habitat suitability of the Rinjani scops-owl on Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 27 (5): d270501. https://doi.org/10.13057/biodiv/d270501. This research models the habitat suitability of the Rinjani scops-owl (Otus jolandae) by identifying key environmental factors influencing its distribution on Lombok Island, Indonesia, through Maximum Entropy (MaxEnt). Field surveys conducted between 2020 and 2023 at 135 sites, using point counts aided by vocalization techniques, yielded 298 detections, which were spatially filtered to 29 distinct occurrence points. The spatial distribution was modeled using four non-collinear environmental predictors: elevation, distance to human settlements, Normalized Difference Vegetation Index (NDVI), and slope. The model's performance was assessed using the Area Under the Receiver Operating Characteristic (AUC-ROC) Curve. A thresholding approach based on the 10th percentile of the training presence (P10) was employed to define the binary suitable habitat distribution from the complementary log-log (cloglog) output. The model achieved a mean AUC of 0.794 (±0.078 SD), indicating a reliable distinction between suitable and unsuitable areas. Elevation emerged as the most significant predictor, contributing 53.4% and having a permutation importance of 50.1%. Suitable habitats were primarily located in mid-elevation forests (600-1,000 m asl) with high NDVI and gentle slopes. The total predicted suitable habitat spanned 2,635.09 km², accounting for approximately 57.7% of the island's total area (4,570.66 km²). The model identified 626.116 km² of high suitability and 528.50 km² of very high suitability, covering both protected and non-protected areas. Areas of moderate suitability (724.334 km²) and low suitability (756.141 km²) were more widespread. Conservation efforts should focus on protecting mid-elevation core habitats by maintaining the canopy to support foraging and breeding. In non-protected areas, targeted restoration and forest patch protection are crucial to expanding suitable habitats, reinforcing buffer zones, and enhancing landscape connectivity.